Bragg reflection and conversion between helical bloch modes in chiral three-core photonic crystal fiber - Loranger, Sebastien; Chen, Yang; Roth, Paul; Frosz, Michael H.; Wong, Gordon Kwan Leung; Russell, Philip St. John (Journal of Lightwave Technology, 2020)
Optical fiber modes carrying orbital angular momentum (OAM) have many applications, for example in mode-division-multiplexing for optical communications. The natural guided modes of N-fold rotationally symmetric optical fibers, such as most photonic crystal fibers, are helical Bloch modes (HBMs). HBMs consist of a superposition of azimuthal harmonics (order m) of order A(m) = A(0) + mN. When such fibers are twisted, these modes become circularly and azimuthally birefringent, that is to say HBMs with equal and opposite values of A(0) and spin s are non-degenerate. In this article we report the use of Bragg mirrors to reflect and convert HBMs in a twisted three-core photonic crystal fiber, and show that by writing a tilted fiber Bragg grating (FBG), reflection between HBMs of different orders becomes possible, with high wavelength-selectivity. We measure the near-field phase and amplitude distribution of the reflected HBMs interferometrically, and demonstrate good agreement with theory. This new type of FBG has potential applications in fiber lasers, sensing, quantum optics, and in any situation where creation, conversion, and reflection of OAM-carrying modes is required.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Fiber bragg gratings; helical bloch modes; orbital angular momentum; twisted fiber

Cross-phase modulational instability of circularly polarized helical Bloch modes carrying optical vortices in a chiral three-core photonic crystal fiber - Roth, Paul; Frosz, Michael H.; Weise, Linda; Russell, Philip St. John; Wong, Gordon Kwan Leung (Optics Letters, 2021)
We report the first, to the best of our knowledge, observation of cross-phase modulational instability (XPMI) of circularly polarized helical Bloch modes carrying optical vortices in a twisted photonic crystal fiber with a three-fold symmetric core, formed by spinning the fiber preform during the draw. When the fiber is pumped by a superposition of left-circular polarization (LCP) and right-circular polarization (RCP) modes, a pair of orthogonal circularly polarized sidebands of opposite topological charge is generated. When, on the other hand, a pure LCP (or RCP) mode is launched, the XPMI gain is zero, and no sidebands are seen. This observation has not been seen before in any system and is unique to chiral structures with N-fold rotational symmetry. The polarization state and topological charge of the generated sidebands are measured. By decomposing the helical Bloch modes into their azimuthal harmonics, we are able to deduce the selection rules for the appearance of modulational instability sidebands. We showed that the four waves in the nonlinear mixing process must exhibit the same set of azimuthal harmonic orders. (C) 2021 Optical Society of America
CRIS-Team WoS Importer:2021-02-12

Vector helical bloch modes in N-fold rotationally symmetric waveguiding structures: Spin and Azimuthal order - Russell, Philip St. John; Chen, Yang; Roth, Paul; Wong, Gordon Kwan Leung (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Many different techniques have been used to model the electromagnetic response of photonic crystal fibres (PCFs) and waveguide arrays. Here we introduce a new vectorial approach based on helical Bloch waves (hBWs) that appear in structures (such as many PCFs) that are N-fold rotationally symmetric (symmetry group Cn), i.e., they repeat perfectly in N sectors over 2π, when viewed in a cylindrical coordinate frame [1]. Helical Bloch waves can also carry optical angular momentum: a complex Bloch wave field propagates azimuthally around the axis of the structure, forming helical Bloch modes (hBMs) when a certain azimuthal resonance condition is satisfied.
CRIS-Team Scopus Importer:2019-11-15